THE EFFECTIVENESS OF ORAL PRESENTATION TECHNIQUE FOR SPEAKING SKILL TO STUDENTS AT SMA NEGERI 1 KOTAMOBAGU - Mellinia P Tawas; Sanerita Olii; Tirza A Kumayas (KOMPETENSI, 2021)
The purpose of this research is to reveal the students speaking skill by the use of the Oral Presentation Technique. This study is carried out on second-grade students at SMA Negeri 1 Kotamobagu during the academic year 2020/2021. A quantitative approach is used in this pre-experimental study. There are 22 students in one class for the subject. The experiment is divided into three stages: pre-test, treatment, and post-test. The instrument of the study is the oral test. The data are obtained by pre-test and post-test. Before giving the treatment, the researchers administer the pre-test to find out students’ speaking skill at the beginning. The post-test is conducted at the end after giving the treatment. In analyzing the obtained data, researchers use the mean score formula. The result shows that the average post-test score (4.09) is the highest of the pre-test score (2.59). This result may lead to a conclusion that the Oral Presentation Technique is effective for students' speaking skills in the second grade at SMA Negeri 1 Kotamobagu.